TSPAN1 functions as an oncogene in gastric cancer and is downregulated by miR‐573. Issue 15 (6th June 2015) - Lu, Zhengmao; Luo, Tianhang; Nie, Mingming; Pang, Tao; Zhang, Xin; Shen, Xiaojun; Ma, Liye; Bi, Jianwei; Wei, Guo; Fang, Guoen; Xue, Xuchao
Abstract : Tetraspanin 1 (TSPAN1) has been reported to be upregulated in gastric cancer (GC). However, whilst TSPAN1 is positively correlated with clinical stage and negatively correlated with survival rates, its function in GC remains elusive. Here we show that expression of TSPAN1 is significantly higher in GC tissues compared to non‐cancerous tissues. Furthermore, we demonstrate that RNAi‐mediated down‐regulation of TSPAN1 expression markedly blocks GC cell proliferation, cell cycle progression and invasive activity. We identified TSPAN1 as a novel target gene of miR‐573. Overexpression of miR‐573 suppressed proliferation and invasion of GC cells by down‐regulation of TSPAN1 expression. Restoration of TSPAN1 rescued the effects of miR‐573 overexpression. Therefore, our findings suggest that the miR‐573/TSPAN1 axis is important in the control of gastric carcinogenesis. Abstract : Knockdown of TSPAN1 inhibits GC cell proliferation and invasion. miR‐573 represses TSPAN1 expression by directly targeting its 3′UTR. miR‐573 regulates GC cell proliferation and invasion. Overexpression of TSPAN1 attenuates miR‐573‐induced inhibition of GC cell proliferation and invasion.